Explaining High Performance Among Indian Administrative Service (IAS) Officers: A Job Demands-Resources Perspective. (June 2023) - Pati, Surya Prakash; Kakani, Ram Kumar
Indian Administrative Service (IAS) officers are careerist senior civil servants (SCS) in the world's largest democracy, holding senior roles of policymaking and implementation. Therefore, identifying exceptionally performing SCS to unravel their "job demands" along with "personal resources" should help with understanding how best to manage these critical human resources. Employing a qualitative approach, we interviewed 11 high performing IAS officers identified through a unique career progression index. Our data analysis revealed that the IAS suffers from the following job demands: difficulty in coordination with other departments and stakeholders, financial inadequacy, and dishonest subordinates or coworkers. This study also found that self-directed learning, personal reputation, empathy, and service orientation are essential personal resources for high-performing SCS. While expanding the list of job demands and personal resources in the public administration context, our research provides a deeper insight into the challenges confronting careerist SCS in lower-middle income developing countries.